Morphological changes of humeral bones at animals with the expressed senile changes at moderate physical loadings - Давибіда [Davibida N.], Наталія Олегівна (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> Application of unique methodical approach and complex of adequate methods of research on large homogeneous experimental material allowed to find out conformities to the law of morpho-functional transformations of structure of long bones of animals which take place in the conditions of the different modes of motive activity in the different age groups. The moderate physical loadings are the factor of inhibition of involutive changes in humeral bones. In the group of young animals the processes of narrowing of plate and multiplying activity of osteoblasts were observed, that mediated showed up multiplying the sizes of bones and their structure at experimental animals. In the group of animals with the expressed senile changes inhibition of mineralization of bone is noticed. It is set that the effect of action of the different modes of motive activity on the processes of morphogenesis depends on age and also intensity and duration of the physical loadings. The results of the conducted research have both theoretical and practical value, as they give a methodical base for the studding of transformations of adaptations in the bone system, determination of range of its transformations. Experimentally confirmed possibility of prognostication of training exercises and dosed physical loadings with the purpose of correction of structural changes to the skeleton depending on age. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->